Copper (CU) and zinc (ZN) in the food web of intertidal mangrove ecosystem of Sungai Puloh, Malaysia - Emeka, Udechukwu Bede (2011)
The purpose of this study was to assess the copper (Cu) and zinc (Zn) levels in the intertidal mangrove sediment of Sungai Puloh (SGP) and Sungai Tengi (SGT). Another aim was to assess the bioaccumulation pattern of Cu and Zn in a food web of Sungai Puloh intertidal mangrove ecosystem. For the first goal,intertidal surface sediment samples were collected from four stations in each of the two intertidal mangrove ecosystems of Sungai Puloh (SGP N 03° 04.786´ E 101° 23.903 and Sungai Tengi (SGT N 03° 24.682, E 101° (997) in Selangor between January and March 2009. For the second objective, different components of intertidal mangrove ecosystem (mangrove leaves, roots, phytodetritus-algae and detritus, surface sediment, crabs, snails and fish) were collected from six stations in Sg. Puloh mangrove between August and December, 2009. The samples were determined for Cu and Zn by using an airacetylene flame Atomic absorption Spectrophotometer (Analyst 800 model, by Perkin-Elmer) and presented in μg/g dry weight basis. The results revealed that both SGP and SGT with mean Zn concentrations (302.64 ± 5.33 μg/g) and (870.73± 61.04 μg/g) respectively were contaminated by Zn, while only SGP showed elevated levels of Cu (67.17±4.95μg/g), and receives more anthropogenic inputs of Cu (27.0%) and Zn (63.4%) compared to SGT with anthropogenic inputs of Cu (13.2%) and Zn (31.4%) with a significant difference (P < 0.05). It was also found in Sungai Puloh that there is a positive correlation between the trophic chains with evidence of biomagnifications of Cu in Uca annulipes – phytodetrtus chain (biomagnifications factor BMF 2.83, r = 0.422 P > 0.05) and that of Zn was observed only in Periophthalmodon schlosseri gill – U. annulipes chain (BMF 1.53, r = 0.130 P > 0.05). In conclusion, Sungai Puloh intertidal mangrove surface sediment is moderately contaminated and receives more anthropogenic inputs of Cu and Zn compared to Sungai Tengi intertidal mangrove surface sediments. Even though Cu and Zn accumulate in the organisms and showed high concentration in SGP intertidal mangrove surface sediment, it has not reached its toxic level in the food web of this intertidal mangrove ecosystem. However, due to the economic importance of these mangroves in supporting a variety of marine and terrestrial life including local fishery activities, there is an urgent need to take actions by the appropriate authorities to protect SGP intertidal mangrove ecosystem from anthropogenic contaminants, while SGT intertidal mangrove ecosystem should be monitored periodically.